Seasonal photochemical transformations of nitrogen species in a forest stream and lake - Porcal, Petr; Kopáček, Jiří; Tomková, Iva (PloS one, 2014)
The photochemical release of inorganic nitrogen from dissolved organic matter is an important source of bio-available nitrogen (N) in N-limited aquatic ecosystems. We conducted photochemical experiments and used mathematical models based on pseudo-first-order reaction kinetics to quantify the photochemical transformations of individual N species and their seasonal effects on N cycling in a mountain forest stream and lake (Plešné Lake, Czech Republic). Results from laboratory experiments on photochemical changes in N speciation were compared to measured lake N budgets. Concentrations of organic nitrogen (Norg; 40-58 µmol L-1) decreased from 3 to 26% during 48-hour laboratory irradiation (an equivalent of 4-5 days of natural solar insolation) due to photochemical mineralization to ammonium (NH4+) and other N forms (Nx; possibly N oxides and N2). In addition to Norg mineralization, Nx also originated from photochemical nitrate (NO3-) reduction. Laboratory exposure of a first-order forest stream water samples showed a high amount of seasonality, with the maximum rates of Norg mineralization and NH4+ production in winter and spring, and the maximum NO3- reduction occurring in summer. These photochemical changes could have an ecologically significant effect on NH4+ concentrations in streams (doubling their terrestrial fluxes from soils) and on concentrations of dissolved Norg in the lake. In contrast, photochemical reactions reduced NO3- fluxes by a negligible (<1%) amount and had a negligible effect on the aquatic cycle of this N form.
Keywords: železo; Iron; Nitrogen; dusík; Forests; lesy; řeky; Lakes; Rakousko; jezera; Rivers; Austria; Kinetics; roční období; teoretické modely; Seasons; Czech Republic; Photochemical Processes; Models, Theoretical; Česká republika; kinetika; fotochemické procesy